Visualizing hydrogen-induced reshaping and edge activation in MoS2 and Co-promoted MoS2 catalyst clusters - Signe S. Grønborg (Nature Portfolio, 2018)
Rational design of a hydrodesulfurization catalyst relies on a fundamental understanding of its working principles. Here, the authors use scanning tunneling microscopy to directly visualize and quantify hydrogen-induced reshaping and edge activation in MoS2 and Co-promoted MoS2 catalyst clusters.